2022
DOI: 10.1177/20552076221143234
|View full text |Cite
|
Sign up to set email alerts
|

Associations between smartphone keystroke dynamics and cognition in MS

Abstract: Objective Examine the associations between smartphone keystroke dynamics and cognitive functioning among persons with multiple sclerosis (MS). Methods Sixteen persons with MS with no self-reported upper extremity or typing difficulties and 10 healthy controls (HCs) completed six weeks of remote monitoring of their keystroke dynamics (i.e., how they typed on their smartphone keyboards). They also completed a comprehensive neuropsychological assessment and symptom ratings about fatigue, depression, and anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…During a typing analysis with a custom on-screen smartphone keyboard, the MS group had slower typing speed, which was also associated with processing speeds. 109 Furthermore, PwMS with better cognitive function showed a higher correlation between backspace and autocorrection events. 109 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…During a typing analysis with a custom on-screen smartphone keyboard, the MS group had slower typing speed, which was also associated with processing speeds. 109 Furthermore, PwMS with better cognitive function showed a higher correlation between backspace and autocorrection events. 109 .…”
Section: Resultsmentioning
confidence: 95%
“…109 Furthermore, PwMS with better cognitive function showed a higher correlation between backspace and autocorrection events. 109 . Hilty et al found an association between heart rate variability and disease severity in PwMS through 24-hour monitoring with a wearable device 110 .…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, a promising research field is the study of the interaction with digital devices in neurodegenerative pathologies, such as Parkinson’s disease [ 41 ] or multiple sclerosis [ 42 ]. In fact, according to new research data, tap speed (how quickly one types on a smartphone keyboard) may be a useful tool for monitoring multiple sclerosis severity [ 43 , 44 ]. Thus, we cannot exclude the application of the prospective analysis of operator–VDU interaction with our system to promote early diagnosis of neurodegenerative alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Even with mild disease severity and with a shorter disease duration in patients with MS, distinctions between controls and patients were already apparent. Another study also examined the relationship between keystroke dynamics and cognitive functioning in participants with MS [ 48 ]. They found that typing speed and use of the backspace key along with autocorrection events correlated with a better cognitive functioning and less severe symptoms.…”
Section: Keystroke Dynamics and Affected Cognitive Domains In Neurode...mentioning
confidence: 99%